Austerity and Private Debt - Mathias Klein (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Based on a panel of OECD countries, I provide empirical evidence that the costs of austerity crucially depend on the level of private indebtedness. In particular, fiscal consolidations lead to severe contractions when implemented in high private debt states. Contrary, fiscal consolidations have no significant effect on economic activity when private debt is low. These results are robust for alternative definitions of private debt overhang, the composition of fiscal consolidations and controlling for the state of the business cycle and government debt overhang. Private debt-dependent responses are mainly driven by household debt, whereas the effects differ only slightly with the level of corporate debt. Moreover, in high private debt states austerity induces a substantial fall in house prices. Both of these latter findings indicate that deterioration in household balance sheets are important to understand private debt-dependent effects of austerity. One possible implication of this paper is that the negative effects of large-scale fiscal consolidations undertaken by Southern European countries were likely to be amplified by the high private debt burdens in these economies.
Keywords: C23; E32; E62; 330